PROFIL BERPIKIR KRITIS SISWA KELAS VIII MTs ALKHAIRAAT MALENI DALAM MENYELESAIKAN SOAL SISTEM PERSAMAAN LINEAR DUA VARIABEL: Critical Thinking Analysis Of Class VIII Students At Mts Al Khairaat Maleni In Solving Problems Of Two Variables Linear Equation System - Mardiana, Nanang; Paloloang, Baharuddin; Hasbi, Muh.; Rochaminah, Sutji (Universitas Tadulako, 2025)
This study aims to obtain a description of students' critical thinking in solving problems on the system of linear equations of two variables at MTs Alkhairaat Maleni. This type of research is descriptive with a qualitative approach. The subjects in this study were students of class VIII B MTs Alkhairaat Maleni consisting of three people, namely one student each with high, medium and low mathematics abilities. Data collection techniques used written tests and interviews. The results of this study indicate that (1) The critical thinking profile of subjects with high mathematics ability is a subject who is able to master the FRISCO indicators (focus, reason, inference, situation, clarity, and overview). Subjects with moderate mathematics ability are subjects who only partially master the FRISCO indicators, namely the subject does not provide the right reasons to support the conclusions he makes (reason). The subject determines the steps to solve the problem. But the subject is less precise in concluding the solution to the problem (inference). The subject with low mathematics ability, namely the subject who also partially mastered the FRISCO indicator, namely the subject also gave inappropriate reasons to support the conclusions he made (reason). The subject determines the first step in solving the problem. But in solving the problem the subject is not correct in determining the solution strategy (inference). The subject did not use all the information that was in accordance with the problem in the problem (situation). The subject did not recheck what had been done (overview).